STATE, MASS MEDIA AND GLOBAL TERRORISM: CONTEXTUALIZING COMMUNICATION POLICY IN THE LIGHT OF WESTGATE AND OTHER TERROR STRIKES IN KENYA - GM, MURIUKI ROBERT (IJRDO-Journal of Applied Science, 2016)
This paper examines the trilateral communication relationship between the state, mass media andglobal terrorism, in light of the Westgate Shopping Mall in Nairobi and other terror attacks inKenya. The paper looks at the dilemma of the state and the mass media when they unwittinglypropagate the terrorists’ agenda. Through analyzing newspaper reports, published journals andbooks, this paper shows how this set of three actors differ in their communication needs. Themedia looks at terrorism as a source of news while terrorists yearn for the exposure they get fromtheir terror acts in a symbiotic relationship that is difficult to annul. The paper gives a raft ofrecommendations that would see the state work with the media to curb the impact of terrorism.